Gene Therapy for Rdh12-Associated Retinal Diseases Helps to Delay Retinal Degeneration and Vision Loss - Bian J; Chen H; Sun J; Cao Y; An J; Pan Q; Qi M (Dove Medical Press, 2021)
Jiaxin Bian,1,2 Hongyu Chen,1,2 Junhui Sun,1,2 Yuqing Cao,3 Jianhong An,3 Qing Pan,4 Ming Qi1,2,5- 8 1Department of Cell Biology and Medical Genetics, School of Medicine Zhejiang University, Hangzhou, 310000, People's Republic of China; 2Center for Precision Medicine, Zhejiang-California International NanoSystems Institute, Hangzhou, 310000, People's Republic of China; 3School of Optometry and Ophthalmology Wenzhou Medical College, Wenzhou, People's Republic of China; 4Department of Ophthalmology, Zhejiang University Medical School First Affiliated Hospital, Hangzhou, 310000, People's Republic of China; 5Assisted Reproduction Unit, Department of Obstetrics and Gynecology, Department of Laboratory Medicine, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Key Laboratory of Reproductive Dysfunction Management of Zhejiang Province, Hangzhou, 310000, People's Republic of China; 6DIAN Diagnostics, Hangzhou, 310000, People's Republic of China; 7Department of Pathology and Laboratory of Medicine, University of Rochester Medical Centre, Rochester, NY, 14609, USA; 8HVP-China, Hangzhou, 310000, People's Republic of ChinaCorrespondence: Qing PanDepartment of Ophthalmology, Zhejiang University Medical School First Affiliated Hospital, 79 Qingchun Road, Hangzhou, People's Republic of ChinaTel +86 13515814709Email panqing@hotmail.comMing QiDepartment of Cell Biology and Medical Genetics, School of Medicine Zhejiang University, Research Building A713, Yuhangtang Road 866, Hangzhou, People's Republic of ChinaTel +86 13666686943Fax +86 57188208274Email mingqi@zju.edu.cn; ming_qi@urmc.Rochester.eduPurpose: The aim of study was to establish Rdh12-associated inherited retinal disease (Rdh12-IRD) mouse model and to identify the best timepoint for gene therapy.Methods: We induced retinal degeneration in Rdh12−/− mice using a bright light. We clarified the establishment of Rdh12-IRD mouse model by analyzing the thickness of retinal layers and electroretinography (ERG). Rdh12-IRD mice received a subretinal injection of adeno-associated virus 2/8-packaged Rdh12 cDNA for treatment. We evaluated the visual function and retinal structure in the treated and untreated eyes to identify the best timepoint for gene therapy.Results: Rdh12-IRD mice showed significant differences in ERG amplitudes and photoreceptor survival compared to Rdh12+/+ mice. Preventive gene therapy not only maintained normal visual function but also prevented photoreceptor loss. Salvage gene therapy could not reverse the retinal degeneration phenotype of Rdh12-IRD mice, but it could slow down the loss of visual function.Conclusion: The light-induced retinal degeneration in our Rdh12−/− mice indicated that a defect in Rdh12 alone was sufficient to cause visual dysfunction and photoreceptor degeneration, which reproduced the phenotypes observed in RDH12-IRD patients. This model is suitable for gene therapy studies. Early treatment of the primary Rdh12 defect helps to delay the later onset of photoreceptor degeneration and maintains visual function in Rdh12-IRD mice.Keywords: Rdh12, retinal diseases, mouse model, gene therapy